The Engulfing Mother in Indian Mythology: Masculinity and Conflicting Desires. Issue 1 (June 2016) - Kakar, Sudhir
The article describes a key complex of male Hindu development in India that is often met with in clinical work and in products of Hindu cultural imagination. This complex, which the author calls 'maternal enthrallment', has deep influence on adult male attitudes towards women in India. The article explores the three elements of maternal enthrallment through an analysis of well-known and popular myths and legends of Hindu India.